National Early Warning Score 2 provides independent prognostic information in patients hospitalized with heart failure with preserved ejection fraction. (3rd October 2022) - Berge, K; Brynildsen, J; Roysland, R; Christensen, G; Hoiseth, A D; Rosjo, H; Omland, T
Abstract: Background: Heart failure (HF) hospitalisation is a strong predictor of long-term mortality among HF patients. Current European Society of Cardiology HF guidelines do not include recommendations for post-discharge long-term risk prediction for acute HF, despite several cardiac biomarkers and clinical scoring systems being able to predict long-term prognosis. In Europe, the clinical scoring system National Early Warning Score 2 (NEWS2) is increasingly being used for in-hospital risk prediction, and several recent studies have demonstrated a potential to utilize NEWS2 for long-term risk prediction. Purpose: To assess the long-term prognostic accuracy of NEWS2 in patients hospitalised with acute HF in comparison to N-terminal pro-B-type natriuretic peptide (NT-proBNP) and high-sensitivity cardiac troponin T (hs-cTnT), and their differences in prognostic accuracy for HF subgroups with reduced (HFrEF) and preserved (HFpEF) ejection fraction. Methods: In the Akershus Cardiac Examination 2 Study, we measured hs-cTnT and NT-proBNP and calculated NEWS2 within 24 hours of admission in patients hospitalised due to acute dyspnea (n=314). Patients with acute HF as adjudicated index diagnosis were included in the current sub-study (n=143). We assessed post-discharge long-term risk of all-cause mortality by receiver operating characteristic (ROC) analysis and Cox regression models. Results: During median follow-up of 26 (quartile 1–3 8–33) months, 66 patients (46%) died. Patients with poor prognosis had higher NEWS2 (mean 5.9 vs 4.4 points, p=0.004), hs-cTnT concentrations (median 49 vs 27 ng/L, p=0.002), and NT-proBNP concentrations (median 5776 vs 2593 ng/L, p<0.001) compared to patients with favourable prognosis. Stratified by HF subgroups, the area under the ROC curve (ROC AUC) for NEWS2 to predict mortality was superior for HFpEF (ROC AUC 0.79, 95% CI 0.66–0.92) compared to HFrEF (ROC AUC 0.57, 95% CI 0.45–0.69; p=0.012) (Figure). In contrast, prognostic accuracy in HFrEF and HFpEF were comparable for hs-cTnT (ROC AUC 0.64 vs 0.67, p=0.76) and NT-proBNP (ROC AUC 0.72 vs 0.71, p=0.94) (Table). After adjustment for age, sex, body mass index, systolic blood pressure, history of coronary artery disease and estimated glomerular filtration rate, NEWS2 was associated with mortality for HFpEF patients (HR 1.37, 95% CI 1.13–1.66), while no association was found for NEWS2 to predict mortality in HFrEF patients (HR 1.03, 95% CI 0.93–1.15; p for interaction=0.016). Conclusion(s): NEWS2 is a superior prognostic marker among patients hospitalised with HFpEF compared to HFrEF and might be a valuable and readily available tool to prognosticate patients at hospital discharge. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Research grant from the Norwegian Research Council and internal grants from Akershus University Hospital to Torbjørn Omland and Helge Røsjø.